The evolved self : mapping an understanding of who we are - Robertson, Lloyd Hawkeye, 1950- (Health and society, 2020)
"In this work the self, which is core to such concepts as self-esteem and self-actualization, is mapped using elemental units of culture called memes. To understand this self, we draw on western philosophy, major schools of psychology, and the cross-cultural experience of the self in both collectivist and individualist cultures. With this grounding a diverse sample of eleven selves representing three genders are mapped and analyzed grouped in the following clusters: 1) North American selves built through participation in sports, 2) selves centered on notions of North American aboriginality, 3) selves of individuals following a secular humanist paradigm, and 4) selves from China and Russia. Two methods of self-mapping are described. The results support a hypothesis that a healthy or functional self is composed of fundamental elements including constancy, volition, uniqueness, productivity, intimacy, and social interest. The application of this research and the method of self-mapping to counselling and psychotherapy are explored. A disciplinary paradigm is proposed uniting major schools of psychotherapy. This work will be of interest to philosophers, psychologists, social workers, sociologists and all who have wondered how they come to define themselves in the ways that they do."--